Distribution and background levels of mercury in Arctic and Antarctic ecosystems - Zvěřina, O.; Coufalík, P. (Pavel); Krajcarová, L.; Sychová, D.; Komárek, J. (2014)
In presented study, trace levels and geographical distribution of mercury in polar ecosystems were assessed.